Public Acceptance of Nature-Based Solutions for Natural Hazard Risk Reduction: Survey Findings From Three Study Sites in Europe - Anderson, Carl C.; Renaud, Fabrice G.; Hanscomb, Stuart; Munro, Karen E.; Gonzalez-Ollauri, Alejandro; Thomson, Craig S.; Pouta, Eija; Soini, Katriina; Loupis, Michael; Panga, Depy; Stefanopoulou, Maria (Frontiers in Environmental Science, 2021)
Climate change is one factor increasing the risk of hydro-meteorological hazards globally. The use of nature-based solutions (NbS), and more specifically ecosystem-based disaster risk reduction measures (Eco-DRR), has become a popular response for risk reduction that also provides highly-valued co-benefits. Public acceptance is important for NbS since they often rely on local collaborative implementation, management, and monitoring. Although public engagement is a common goal of NbS projects, it is rarely carried out with a sufficient understanding of the (de)motivating factors tied to public perceptions. Successful collaboration demands consideration of societal attitudes and values in relation to risk, nature, and place. However, existing research does not sufficiently explore these themes together, their interactions, and their implications. This may lead to misaligned public expectations and failed participatory initiatives, while jeopardizing the success of NbS projects and their continued funding and uptake. We conducted citizen surveys within local NbS “host” communities to determine the degree of pro-NbS attitudes and behavior, associated variables, and how these may be leveraged to increase acceptance. We compared results across sites, relying primarily on correlations and regression models along with survey comments and expert knowledge. Three distinct rural NbS being implemented within the OPERANDUM project aim to reduce risk from (socio-)natural hazards in Scotland (landslides and coastal erosion; n=66 respondents), Finland (eutrophication and algal blooms; n=204) and Greece (river flooding and water scarcity; n=84). Our research thus centers on rural NbS for risk reduction within a large EU project. Trust in implementers is a consistent factor for defining attitudes towards the NbS across the sites, and attitudes are strongly associated with respondents’ commitment to nature and behavioral acceptance (i.e., willingness to engage). Behaviorial acceptance is most consistently predicted by connectedness to place and the extent of expected future impacts. Skepticism of NbS effectiveness leads to high public demand for relevant evidence. To increase public acceptance, we recommend greater framing of NbS in relation to place-based values as well as demonstration of the effectiveness of NbS for risk reduction. However, distinct hazard types, proposed NbS, and historical characteristics must be considered for developing strategies aimed at increasing acceptance.